Headroom and human trampling : cave ceiling-height determines the spatial patterning of stone artefacts at Petzkes Cave, northern New South Wales - Theunissen, Robert
Going into a cave or shelter, one walks where one can stand upright or has to crouch less. That affects which zones objects are trampled on, which zones they may be kicked out of, which zones they may be kicked into. And those effects interact with the usual spatial orderÐwith its activity zones and drop zonesÐthat develops through occupation of the enclosed cave or shelter.